Collaborative Ethnography as a Possibility of Developing Visible and Constructive Agency with Children in Displacement Conditions in Colombia - Guerrero, Alba-Lucy (Acta Paedagogica Vilnensia, 2017)
The importance of researching children has been recognized by different disciplines; however, this does not necessarily lead researchers to incorporate children’s perspectives and views into the research processes. Traditionally, the understanding of children’s experiences has been conducted from the perspective of adults who are able to speak for them, while children have hardly been taken seriously on their own terms. However, during the 1980s, strategies to combat ways of silencing children expanded in social science research across different disciplinary traditions and paradigms. This paper attempts to delve into the question of active participation of children in the production of knowledge, and the possibilities it opens for both making visible and developing children´s agency. Drawing on a study that examines the ways children displaced by the armed conflict recreate the meanings of their physical and cultural worlds in a violent and impoverished area in Colombia, I will explore the implications of children’s active participation in research. This paper demonstrates that collaborative research provides an opportunity for children to demonstrante their agency in shaping their worlds. Making visible the collaborative research contributions in the Colombian context has a potential of enhancing conceptualizations of research as a form of action that fosters social transformation.